THEORETICAL FOUNDATIONS AND WAYS TO INCREASE COMPETITIVENESS IN THE ECONOMY - Akramova Aziza Abduvohidovna (American Journals Publishing, 2023)
Competitiveness is the capability a country or company has to achieve profitability in the market in relation to its competitors. Competition is a multifaceted economic phenomenon that expresses a complex relationship between all subjects of the market. The article provides an explanation of the role of effective competition in the economy and the improvement of competitive relations.
Keywords: Competitive relations, profitability, monopoly, resources, innovative task, profit, principles and methods, globalization, competitive advantages, effective innovation, increasing the competitiveness, macroeconomic stability, global competitiveness.